Robust design of a side impact beam - Björnström, Sara (2013)
Automobile manufacturers are increasingly facing customer demands on safer vehicles at the same time as requirements on performance, emission and fuel efficiency are increasing. Gestamp Hardtech is a world leading company in press-hardening technology that allows manufacture of hot and cold-formed high-strength lightweight automotive components such as side impact beams, bumpers and body components. Gestamp Hardtech works with customers such as Ford, GM, VW, Volvo and BMW.This master thesis was conducted at Gestamp Hardtech in Luleå at the Department of Research and Development, Body in White (BIW). The objective of this master thesis was to examine which factors affect the deformation behavior of a side impact beam. For side-on collisions there are a risk of the side door collapsing into the passenger compartment injuring the driver or passenger. To prevent intrusion of the side door and personal injuries a side impact beam is attached inside the side door. The side impact beam absorbs energy during deformation and distributes forces to strong surrounding structures. Experimental design was chosen as the method to examine which factors affect the deformation behavior of a side impact beam. The work process of experimental design was implemented and the result of the experimental design proved that profile height, length of side impact beam and springs have the greatest affect on the deformation behavior of a side impact beam. Validerat; 20130624 (global_studentproject_submitter)